Cigarette fatwas, contestation of religious authority and politics in Indonesia - Saifuddin Zubaidi (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
The issuance of non-binding advisory opinions (fatwa) is always followed by the presence of new issues related to the implementation of the fatwa. Similarly, the smoking ruling was issued by the Council of Indonesian Scholars (MUI) at the Conference in Padang Panjang in 2009. More than a decade this subject is still debatable. Although the fatwa in Indonesia does not have the power of binding, for Muslims, the idea of religious morality remains a consideration in daily life. Through a literature study, this study will reveal how the problematic relations between various social agencies regarding the issuance of the cigarette fatwa. Discourse debates in the study of fiqh will begin the explanation of this study, followed by development policies in Indonesia related to the problem of cigarettes, and ended with the position of the ulema as the holder of religious authority in the matter of smoking. This study illustrates that the practice of fatwas will be effective when ulama as religious authority holders, with their